Prevalence and Prognostic Value of Malnutrition Among Elderly Cancer Patients Using Three Scoring Systems - Zhang, Qi; Qian, Liang; Liu, Tong; Ding, Jia-Shan; Zhang, Xi; Song, Meng-Meng; Wang, Zi-Wen; Ge, Yi-Zhong; Hu, Chun-Lei; Li, Xiang-Rui; Tang, Meng; Wang, Kun-Hua; et al. (Frontiers in Nutrition, 2021)
Background Malnutrition is common in patients with cancer and associated with adverse outcome, but few data exist in elderly patients. The aim of this study was to report the prevalence of malnutrition using three different scoring system, and to examine the possible clinical relationship and prognostic consequence of malnutrition in elderly patients with cancer. Methods This is a secondary analysis using an ongoing prospective cohort study data in China. Nutritional status was assessed by using controlling nutritional status (CONUT), the prognostic nutritional index (PNI), and the nutritional risk index(NRI). Quality-of-life was assessed at the admission by using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C-30. Performance status(PS) was assessed by using the Eastern Cooperative Oncology Group(ECOG) classification. The relationship between nutritional status and overall survival and quality-of-life were examined. Results Data were available for 1,494 elderly patients with cancer (63.65% male), the mean age was 70.76 years. According to the CONUT, NRI, and PNI, 55.02%, 58.70%, and 11.65% patients were diagnosed with malnutrition. Worse nutritional status was related to older, lower BMI, lower hand grip strength and more advanced tumor stage. All malnutrition indexes were correlated with each other (CONUT vs PNI, r=-0.657; CONUT vs NRI scores, r= -0.672; PNI vs NRI scores, r=0.716, all P<0.001). During a median follow-up of 43.1 months, 692(46.32%) patients died. For patients malnourished, the incidence rate (events-per-1000-person-years) were as follow: CONUT(254.18), PNI(429.91), and NRI(261.87). Malnutrition was associated with increased risk for all-cause mortality(adjust HR[95%CI] for CONUT: 1.09[1.05-1.12],P<0.001; PNI:0.98[0.97-0.99],P<0.001; NRI:0.98[0.98-0.99],P<0.001). All malnutrition indexes improve the predictive ability of the TNM classification system for all-cause mortality. Deterioration of nutritional status was associated with deterioration in quality-of-life parameters and immunotherapeutic response(P<0.001). Conclusions Malnutrition was prevalent in elderly patients with cancer regardless of the assessment tools used, and associated with lower quality of life and the immunotherapy response.